(3eNJUQ eSGFd Mfjfs - (3CHh Sgd SYjO Hf YHO GdYRjR Gdfjdis; (3Mfjf Hf ESMGb GdYHGOqj, CHh RjO,J (B260 (3g` s
(3ChdgG (B:s
(3bGd TcG Edi LeGYI ef GdCNhGfi UYhHI JMaX GdeSGFd GdefShHI Edi Mfjf GdaUd GdChd GdWH jfbSe Edi Yde fXQi s
(3BNQgG (B:s
(3ef Cf jchf eJSGhjjf Ch CMOgeG GdWH hGdYde Je s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdQGHYIs
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B287 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B87s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1668s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdWHs